State Action Antitrust Exemption in a Context of Deregulation of the Telecommunications Sector: An Analysis of CADE’s VU-M Case - Caixeta, Deborah Batista (Law, State and Telecommunications Review, 2014)
Purpose ”“ The purpose of this essay is to examine CADE’s behavior in relation to regulatory measures adopted by ANATEL in fixing the mobile interconnection rate (Portuguese acronym VU-M), from the perspective of the State Action Doctrine in the context of deregulation of the telecommunications industry in Brazil. Methodology/approach/design ”“ The paper presents an approach to the theories of deregulation of telecommunications industry and the impact that antitrust exemptions have on this movement from the perspective of the VU-M Case recently ruled by CADE. Findings ”“ The granting of antitrust exemptions by CADE still seems to follow the traditional application of the State Action Doctrine focused on regulatory theory of public interest and, therefore, the utmost confidence in the performance of the agency ends up hindering the process of deregulation, particularly in the telecommunications industry, characterized by the traditional oligopolistic regulatory structure. Practical implications ”“ This review provides an introductory approach that can be applied later to revisit the limits of application of antitrust law to situations covered up by sectorial regulatory measures. Originality/value ”“ This essay points to elements that can be applied in the dynamic interaction between sectorial regulation and competition regulation. This approach allows the traditional structure of application of competition rules to regulated sector to be redesigned to incorporate the objectives pursued by the movement of deregulation in telecommunications industry.